2008
DOI: 10.1007/s00122-008-0721-7
|View full text |Cite
|
Sign up to set email alerts
|

Niger-wide assessment of in situ sorghum genetic diversity with microsatellite markers

Abstract: Understanding the geographical, environmental and social patterns of genetic diversity on different spatial scales is key to the sustainable in situ management of genetic resources. However, few surveys have been conducted on crop genetic diversity using exhaustive in situ germplasm collections on a country scale and such data are missing for sorghum in sub-Saharan Africa, its centre of origin. We report here a genetic analysis of 484 sorghum varieties collected in 79 villages evenly distributed across Niger, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
84
9
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(130 citation statements)
references
References 50 publications
22
84
9
13
Order By: Relevance
“…Nonetheless, our results are similar to that of Sagnard et al (2011) (7.48 alleles in average per locus) who worked on 455 sorghum accessions from Mali and Guinea using 15 SSR markers. However, the average number calculated in the present study was lower than that reported by Deu et al (2008) and Bhosale et al (2011), which were 10.43 and 19, respectively from 472 accessions of sorghum from Niger and 219 accessions of sorghum cultivated in West Africa and assessed by means of 28 and 27 SSR markers, respectively.…”
Section: Overall Genetic Diversitycontrasting
confidence: 87%
See 1 more Smart Citation
“…Nonetheless, our results are similar to that of Sagnard et al (2011) (7.48 alleles in average per locus) who worked on 455 sorghum accessions from Mali and Guinea using 15 SSR markers. However, the average number calculated in the present study was lower than that reported by Deu et al (2008) and Bhosale et al (2011), which were 10.43 and 19, respectively from 472 accessions of sorghum from Niger and 219 accessions of sorghum cultivated in West Africa and assessed by means of 28 and 27 SSR markers, respectively.…”
Section: Overall Genetic Diversitycontrasting
confidence: 87%
“…Before the advent of GBS-based single nucleotide polymorphism (SNP) markers and additionally other whole-genome profiling markers (for example DArT), microsatellite markers are the most used worldwide in the characterization of sorghum genetic resources and particularly in genetic diversity analysis (Smith et al, 2000;Folkertsma et al, 2005;Barnaud et al, 2007;Deu et al, 2008;Barro-Kondombo et al, 2010;Bhosale et al, 2011). In Benin, although AFLP markers were used in genetic characterization of sorghum local varieties (Kayodé et al, 2006), it is the first time SSR markers were used for sorghum germplasm analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that farmers' seed sharing networks drive the gene flow of crops within a region [9,17,18,50]. Access to diverse crop germplasm requires that farmers have adequate income or connections without social or political constraints to acquire different crop varieties [51].…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood groups [9] and marriage exchanges are other social factors that shape crop diversity at local and regional levels [16][17][18][19].…”
mentioning
confidence: 99%
“…Dentre elas, tem-se: (i) construção de mapas genéticos e mapeamento de QTLs para características quantitativas importantes -Mace and Jordan (2010) apresentam uma ampla revisão sobre esses estudos; (ii) análise do desequilíbrio de ligação (Hamblin et al, 2004(Hamblin et al, , 2007Bouchet et al, 2012;Morris et al, 2013) e mapeamento associativo (Casa et al, 2008;Sukumaran et al, 2012;Morris et al, 2013); (iii) análise da diversidade genética e do fluxo gênico entre populações (Morden et al, 1989(Morden et al, , 1990Agrama and Tuinstra, 2004;Casa et al, 2005;Folkertsma et al, 2005;Deu et al, 2006Deu et al, , 2008de Alencar Figueiredo et al, 2008;Mutegi et al, 2011;Sagnard et al, 2011;Bouchet et al, 2012); e (iv) estimação de taxas de recombinação Morris et al, 2013) e seleção Casa et al, 2006;Bouchet et al, 2012 Nos últimos anos, a descoberta de marcadores moleculares e a genotipagem de centenas de indivíduos têm sido realizadas a partir das novas plataformas de sequenciamento para muitos estudos (Varshney et al, 2009;Davey et al, 2011). Com base em um único procedimento de sequenciamento (Davey et al, 2011), essas plataformas possibilitam a geração de grandes quantidades de dados a uma velocidade bastante superior em comparação com as metodologias tradicionais (Varshney et al, 2009), mostrando eficiência, rapidez e custo reduzido.…”
Section: Marcadores Moleculares E Genotipagem Por Sequenciamentounclassified